Porous Molybdenum Carbide Nanostructured Catalyst toward Highly Sensitive Biomimetic Sensing of H2O2. Issue 6 (12th February 2020) - Li, Juan; Tang, Chun; Liang, Taotao; Tang, Chuyue; Lv, Xiaohui; Tang, Kanglai; Li, Chang Ming
Abstract: There are great challenges to fabricate a highly selective and sensitive enzyme‐free biomimetic sensor. Herein for the first time a unique nanostructure of porous molybdenum carbide impregnated in N‐doped carbon (p‐Mo2 C/NC) is synthesized by using SiO2 nanocrystals‐templating method and is further used as an enzyme‐free electrochemical biosensor toward highly selective, sensitive detection of H2 O2, of which the limit of detection, dynamic detection range and sensitivity accomplish as 0.22 μM, 0.05–4.5 mM and 577.14 μA mM −1  cm −2, respectively, and are much superior to the non‐porous molybdenum carbide impregnated in N‐doped carbon (Mo2 C/NC). The sensor is also used to monitor H2 O2 released from A549 living cells. This work holds a great promise to be used to monitor the presence of H2 O2 in biological research while offering an important knowledge to design a highly selective and sensitive biomimetic sensor by synthesizing a porous catalyst to greatly improve the reaction surface area rather than conventionally only relying on dispersing the catalyst material into porous carbon substrate. Abstract :